SUITABILITY ASSESSMENT OF GROUNDWATER QUALITY FOR DRINKING PURPOSES - Islam, Md. Zahidul; Mostafa, M. G. (UI Scholars Hub, 2024)
The groundwater status of Northwestern Bangladesh is a complex and challenging issue due to its arid and semi-arid climates, increasing population, overexploitation for domestic and irrigation purposes, lack of adequate rainfall, and limited water resources. The study aimed to assess the suitability and health risk of groundwater quality for drinking purposes. A total of one hundred groundwater samples were collected from shallow tubewells in two seasons, the monsoon (MON) and post-monsoon (POM), in northwestern Bangladesh (Ganges River basin) and analyzed using standard methods of analysis (Atomic adsorption spectrometry, UV-visible spectrometry, graphite, ion chromatography). The trends of predominant cations were Ca2+ > Na+ > Mg2+ > K+, and anions were HCO3− > Cl− > SO42− > NO3− > PO43- in both seasons. The dominant cation and anion are Ca2+ and HCO3−, and the water type of the groundwater was Ca-Mg-HCO3. Contamination of trace metals, including Fe, Mn, and Pb, in the groundwater of the study area follows the trend of Fe > Mn > Pb in two seasons. The study observed that the POM showed a higher concentration of trace metals than the MON season. The results indicated that a higher concentration of Cr, Fe, Mn, Ni, and Pb, as well as the WQI, HMPI, HMEI, and CD posed threats to human health. The quality of the studied samples is poor to undrinkable. The non-carcinogenic risk to human health was not found for both adults and children in both seasons. The study observed that over-extraction, pollution, trace metals, low rainfall, and climate change threaten groundwater quality and availability. The study suggests that groundwater is unfit for human consumption without treatment, particularly for Fe, Mn, and Pb.